2018
DOI: 10.1186/s12974-018-1271-9
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibiting aberrant p53-PUMA feedback loop activation attenuates ischaemia reperfusion-induced neuroapoptosis and neuroinflammation in rats by downregulating caspase 3 and the NF-κB cytokine pathway

Abstract: BackgroundIschaemia reperfusion (IR) induces multiple pathophysiological changes. In addition to its classical role in regulating tumourigenesis, the feedback loop formed by p53 and its driven target p53-upregulated modulator of apoptosis (PUMA) was recently demonstrated to be the common node tightly controlling various cellular responses during myocardial IR. However, the roles of the p53-PUMA feedback loop in the spinal cord remain unclear. This study aimed to elucidate the roles of p53-PUMA feedback interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…Furthermore, the effects of IL-33, mediating apoptotic resistance in astrocytes, are dependent largely on repression of PUMA transcription. These findings are consistent with the recently published results showing that inhibition of aberrant p53-PUMA feedback loop activation by treatment with PUMAspecific siRNA and inhibitor pifithrin-α prevented ischemia reperfusion-induced neuroapoptosis and inflammatory responses [36].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the effects of IL-33, mediating apoptotic resistance in astrocytes, are dependent largely on repression of PUMA transcription. These findings are consistent with the recently published results showing that inhibition of aberrant p53-PUMA feedback loop activation by treatment with PUMAspecific siRNA and inhibitor pifithrin-α prevented ischemia reperfusion-induced neuroapoptosis and inflammatory responses [36].…”
Section: Discussionsupporting
confidence: 93%
“…CA pretreatment also significantly reduced the number of TUNEL-positive cells and significantly reduced NF-κB p65 expression in I/R-injured rats, revealing CA-induced amelioration of inflammation and apoptosis. The nuclear translocations of NF-κB p65 and p53 in different types of I/R injuries, including intestinal I/R injuries, result in inflammation and apoptosis [ 40 , 97 ]. Our results indicated that CA inhibited both NF-κB p65 and p53 nuclear translocation in H/R-injured IEC-6 cells, suggesting that inhibition of nuclear translocation and inhibition of inflammation and apoptosis were involved in CA-induced protection against intestinal I/R injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Transactivation of p53 in the CKD Model. Since p53 is the most critical molecule upstream of Puma and Bax and that the nuclear translocation of p53 represents its activation [18], we extracted the nuclei from the remnant kidney tissues to analyze the protein level of p53 in the nuclear fraction. We found that nuclear p53 content and its phosphorylation (Ser15) were significantly upregulated in rats after 5/6 (A/I) injury (Figures 4(a) and 4(b)).…”
Section: Ssr Suppressed the Nuclear Translocation Andmentioning
confidence: 99%